PENEGAKAN HUKUM ATAS PENIPUAN DALAM JUAL-BELI BAHAN BAKAR MINYAK DI KABUPATEN BELU - Haki, Grasella Listin; Pello, Jimmy; Leo, Rudepel Petrus; Wihelmus, Bhisa Vitus (Petitum Law Journal, 2025)
This study aims to analyze the gap between legal regulations and their practical implementation in fuel sales activities in Belu Regency, as well as to identify various obstacles that hinder the effective enforcement of criminal law against fraudulent actors in these activities. The approach used is an empirical juridical approach with qualitative descriptive methods, examining both the applicable laws and their enforcement in society, particularly concerning fraud practices in fuel distribution and sales. Data were collected through interviews with five attendants of Stasiun Pengisian Bahan Bakar Umum (SPBU), ten consumers, and informal fuel sellers, supported by literature review and relevant regulations. The findings reveal fraudulent practices such as manipulation of fuel volume, failure to reset dispensers to zero before filling, and resale of fuel by consumers. These actions constitute violations of Article 378 of the Indonesian Criminal Code (KUHP) concerning fraud, yet firm legal enforcement remains lacking. This study also identifies several barriers to effective law enforcement, including unclear legal provisions, limited resources of law enforcement officers, inadequate supporting infrastructure, low public legal awareness, and a cultural tendency to tolerate legal violations. Therefore, this study recommends strengthening law enforcement mechanisms and supervision systems to ensure fuel distribution and sales are conducted fairly, transparently, and responsibly.